Off-farm income and dietary diversity in subsistence farming in Burundi - Emera, Willy Désiré; Lachat, Carl; Umwungerimwiza, Yves Didier; Slosse, Wannes; D’Haese, Marijke (Springer Science+Business Media, 2025)
The impact of agricultural decisions on the dietary diversity of people living on subsistence farms is poorly documented. This study examines the relationship between diversity in agricultural production and diets in two provinces of northern Burundi. The factors associated with the dietary diversity of women and children in these rural households were analysed using Poisson and probit models with six indicators of agricultural production diversity: (1) tropical livestock units, (2) animal count, (3) crop species count, (4) the Simpson’s index, (5) the Shannon index and (6) caloric content. We distinguish three groups of farms based on the proportion of agricultural products sold, i.e., "subsistence farms” sold less than 5%, “quasi-subsistence farms” sold between 5 and 10%, and “farms with some sales” sold more than 10% of their produce. On average, women on subsistence farms consumed 4.0 out of ten food groups (standard deviation: 1.54), which is lower than the averages of 4.8 (standard deviation: 2